Numerical study of the response of dynamic parameters to defects in composite structures - Grigorii S. Serovaev; Valery P. Matveenko (Fracture and Structural Integrity)
The purpose of this work is to study three different models of delamination in composite plate (the free mode model, the constrained model and the contact model) and applicability of this models to the vibrational method of damage detection based on frequency shifts. The results of numerical simulation have shown that the free mode model leads to abrupt changes in natural frequencies due to non-physical condition of mutual penetration of adjacent volumes in the defect zone. The constrained and the contact models yield qualitative agreement in shifts of natural frequencies with a change of the defect size. All models have shown the necessity of analyzing shifts of high frequencies to detect small size delamination